The Impact of Hidden Structure on Aggregate Disassembly by Molecular Chaperones - Shoup, Daniel; Roth, Andrew; Puchalla, Jason; Rye, Hays S. (Frontiers in Molecular Biosciences, 2022)
Protein aggregation, or the uncontrolled self-assembly of partially folded proteins, is an ever-present danger for living organisms. Unimpeded, protein aggregation can result in severe cellular dysfunction and disease. A group of proteins known as molecular chaperones is responsible for dismantling protein aggregates. However, how protein aggregates are recognized and disassembled remains poorly understood. Here we employ a single particle fluorescence technique known as Burst Analysis Spectroscopy (BAS), in combination with two structurally distinct aggregate types grown from the same starting protein, to examine the mechanism of chaperone-mediated protein disaggregation. Using the core bi-chaperone disaggregase system from E. coli as a model, we demonstrate that, in contrast to prevailing models, the overall size of an aggregate particle has, at most, a minor influence on the progression of aggregate disassembly. Rather, we show that changes in internal structure, which have no observable impact on aggregate particle size or molecular chaperone binding, can dramatically limit the ability of the bi-chaperone system to take aggregates apart. In addition, these structural alterations progress with surprising speed, rendering aggregates resistant to disassembly within minutes. Thus, while protein aggregate structure is generally poorly defined and is often obscured by heterogeneous and complex particle distributions, it can have a determinative impact on the ability of cellular quality control systems to process protein aggregates.